Β-catenin and PPAR-γ levels in bone marrow of myeloproliferative neoplasm: an immunohistochemical and ultrastructural study. (2nd November 2018) - Subotički, Tijana; Mitrović Ajtić, Olivera; Mićić, Mileva; Kravić Stevović, Tamara; Đikić, Dragoslava; Diklić, Miloš; Leković, Danijela; Gotić, Mirjana; Čokić, Vladan P.
ABSTRACT: In accordance with increased proliferation in myeloproliferative neoplasm (MPN), the goal is to evaluate the immunoexpression of: β-catenin, PPAR-γ and Ki67 protein, to compare them with bone marrow ultrastructural characteristics in patients with MPN. Immunoexpression and electron microscopy of bone marrow was analyzed in 30 Ph-negative MPN patients, including per 10 patients with polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF). The quantity of β-catenin immunoreactive cells was significantly higher in PV then in ET (p < 0.01) or PMF group of patients (p < 0.01) and also in ET versus PMF group of patients (p < 0.01). Erythroid lineage showed absent β-catenin staining without immunoreactivity in nucleus. In contrast, immunoreactivity for PPAR-γ was localized mostly in megakaryocytes and the highest number of PPAR-γ immunopositive cells was detected in PMF group of patients. In addition, the proliferative Ki67 index was significantly increased in the PMF and PV patients compared to patients with ET. Also, the megakaryocytes showed abnormal maturation in PMF group of patients as determined by ultrastructural analysis. These results indicated that PV dominantly expressed β-catenin and proliferation marker Ki67 in bone marrow, while PMF is linked preferentially to PPAR-γ immunopositive megakaryocytes characterized by abnormal maturation.